Engaging in Integrity: A Case Study on Leveraging the LMS for Faculty Education - Clark, Angela; Facciolo, Laura; Pavlova, Iryna (Canadian Perspectives on Academic Integrity, 2025)
Expedited by the onset of the COVID-19 pandemic, the learning management system (LMS) has become a fixture in the infrastructure of the post-secondary classroom. This paper presents a case study describing the actions of a centralized Academic Integrity Office (AIO) at a Canadian community college that aimed to promote faculty engagement and support academic integrity education through the LMS. Specifically, we narrate the development and evolution of an LMS-based repository, examining its impacts and offering recommendations for enhancing social learning and community building. Over time, this repository was transformed into a more robust, centralized portal that improved access to academic integrity resources. Viewership increased to approximately 100 daily visitors, highlighting how platform selection influences access, which in turn supports faculty engagement and participation. This work seeks to address a gap in practice and scholarship by exploring how LMS functionalities and institutional portals can be leveraged to foster communication, build community engagement, and support the development of faculty and student academic integrity literacy while also strengthening faculty-practitioner partnerships.